Implications on Nepal’s Foreign Affairs of the Sino-Indian Rapprochement over Lipulekh - Bhattarai, Gaurav (Unity Journal, 2023)
When China and India get closer, will Nepal be uncomfortable with losing its strategic space? The available literature on Sino-Indian conflict and competition in the Himalayan region do not divulge the impacts of Sino-Indian cooperation on Nepal. By examining the Sino-Indian rapprochement over Nepal’s Lipulekh, this study elaborates the implications of India’s and China’s neighborhood policies on Nepal’s foreign policy. In 2015, while Nepal was concentrating on post-earthquake relief, rehabilitation, and reconstruction, China and India—the two Asian geopolitical rivals, decided to use Nepal’s Lipulekh as a trading corridor, without Nepal’s consent. The Sino-Indian agreement over Nepal’s Lipulekh not only stirred controversy in Nepal but also raised questions over the intention of Nepal’s two immediate neighbors. Although 2015 was not the first time that Nepal’s neighbors agreed upon the Lipulekh route, the case of the Sino-Indian rapprochement in Lipulekh is studied and methodologically analyzed under the framework of exploratory research design. By situating Nepal’s case in the conceptual framework of small states, first, this study surveys Nepal’s foreign policy behavior in the context of Nepal’s Gulliverian neighborhood through deductive reasoning. Second, the impacts of the multi-faceted Sino-Indian interactions on Nepal’s foreign policy are identified through inductive reasoning. Finally, the implications of the neighborhood policies of China and India toward Nepal are discussed against the backdrop of the Sino-Indian rapprochement over Nepal’s Lipulekh.